The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1121/1.405850
|View full text |Cite
|
Sign up to set email alerts
|

Active control of sound power using acoustic basis functions as surface velocity filters

Abstract: An improved method of active structural acoustics control is presented that is based on the minimization of the total power radiated from any structure expressed in terms of a truncated series sum. Each term of this sum is related to the coupling between the orthogonal eigenvectors of the radiation impedance matrix (referred to as ‘‘basis functions’’ in this paper) and the structural surface velocity vector. The basis functions act as surface velocity filters. These acoustic basis functions are found to be wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Johnson and Elliott 12 extended their earlier work by showing that a substantial reduction in the radiated power on planar structures was obtained at long wavelengths by volume velocity cancellation, clearly demonstrating a close relationship between volume velocity control and control of the dominant acoustic radiation mode. Naghshineh and Koopmann 13,14 applied the technique to structural active noise control, with the objective of forcing the structure to respond in a forced mode of vibration that coincided with an inefficient acoustic radiation mode ͑termed a ''weak radiator''͒. Naghshineh et al 15 demonstrated a design optimization technique such that a subject structure would naturally respond in a structural mode of vibration coinciding with a weak radiation mode, representing an application of the acoustic modal technique to passive control.…”
Section: Introductionmentioning
confidence: 98%
“…Johnson and Elliott 12 extended their earlier work by showing that a substantial reduction in the radiated power on planar structures was obtained at long wavelengths by volume velocity cancellation, clearly demonstrating a close relationship between volume velocity control and control of the dominant acoustic radiation mode. Naghshineh and Koopmann 13,14 applied the technique to structural active noise control, with the objective of forcing the structure to respond in a forced mode of vibration that coincided with an inefficient acoustic radiation mode ͑termed a ''weak radiator''͒. Naghshineh et al 15 demonstrated a design optimization technique such that a subject structure would naturally respond in a structural mode of vibration coinciding with a weak radiation mode, representing an application of the acoustic modal technique to passive control.…”
Section: Introductionmentioning
confidence: 98%
“…Since then the sound radiation efficiency and active control of thin plate had been studied [6,7]. Based on the acoustic radiation modes and further study about acoustic radiation, ADS (Acoustic Design Sensitivity) analysis [8,9,10] was presented to guide Low Noise Design of structures.…”
Section: Introductionmentioning
confidence: 99%
“…Sensing strategies using velocity information can also be based on so-called radiation modes, 6 which are the vibration patterns of a structure that radiate sound independently in free space [7][8][9][10][11][12][13] or in enclosed spaces. 14,15 The resulting control strategy is optimal with respect to the number of error signals for the controller.…”
Section: Introductionmentioning
confidence: 99%